2020
DOI: 10.1037/tra0000505
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trauma proximity and ruminative response styles on posttraumatic stress and posttraumatic growth following a university shooting.

Abstract: Objective: Shootings in academic settings are associated with the development of both posttraumatic growth (PTG) and posttraumatic stress (PTS) symptoms (Bardeen, Kumpula, & Orcutt, 2013). Traumatic events can challenge an individual's cognitive framework and contribute to the development of PTS and PTG. Intrusive rumination is thought to increase vulnerability to PTS symptoms, whereas deliberate rumination is likely to be associated with PTG. Literature that serves to distinguish the contextual and intraindiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Caution needs to be taken when evaluating such a finding since the present study only involved 14 participants (out of 422) with the latter attribution. The finding may be explained by proximity; an early study among mass university shooting victims showed that higher proximity predicted more intense posttraumatic symptoms as well as more PTG (Wozniak, Caudle, Harding, Vieselmeyer, & Mezulis, 2020). Accordingly, those who believed that COVID-19 was the fundamental cause of death of their loved ones may have higher emotional proximity towards COVID-19, so that they had experienced higher symptoms and growth.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Caution needs to be taken when evaluating such a finding since the present study only involved 14 participants (out of 422) with the latter attribution. The finding may be explained by proximity; an early study among mass university shooting victims showed that higher proximity predicted more intense posttraumatic symptoms as well as more PTG (Wozniak, Caudle, Harding, Vieselmeyer, & Mezulis, 2020). Accordingly, those who believed that COVID-19 was the fundamental cause of death of their loved ones may have higher emotional proximity towards COVID-19, so that they had experienced higher symptoms and growth.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Prior researches have established that rumination may jeopardize mental health and therefore intensify negative moods, together with depression (Chesnut et al , 2020; Bravo et al , 2019; Genet and Siemer, 2012). Furthermore, intrusive rumination can generate post-traumatic stress disorder as soon as a person is confronted with a traumatic experience thus compromising mental health (Wozniak et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that effective coping strategies can protect people from mental illness when faced with adverse situations ( 5 , 8 – 10 ). And the opposite is observed with maladaptive coping strategies, which influence their mental health predisposing them to alterations such as depression and anxiety ( 6 , 11 – 15 ), so repercussions on well-being depend on the type of coping used ( 3 , 16 ).…”
Section: Introductionmentioning
confidence: 99%